2019
DOI: 10.5006/3111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SO2, O2, NO2, and H2O Concentrations on Chemical Reactions and Corrosion of Carbon Steel in Dense Phase CO2

Abstract: Carbon capture, utilization, and storage is expected to be an important method for reducing CO2emissions to prevent global warming. Several species (impurities) could follow the CO2through the capture plant as carry over. It is expected that nitrogen dioxide (NO2), sulfur dioxide (SO2), oxygen (O2), and water (H2O) can be present as impurities (concentrations at the ppmv level) in the captured CO2. The exact composition will depend on the flue gas type, the CO2capturing process, and multiple other parameters. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Hoa et al showed that, at low pressure, the condensation of SO 2 and NO 2 with water resulted in the formation of H 2 SO 4 and HNO 3 , which led to strong pitting and localized corrosion in the presence of H 2 SO 4 , while HNO 3 induced only high general corrosion. This might be related to different corrosion mechanisms as both Hoa et al and Morland et al suggested, but it could also be an indication of a difference in solubility.…”
Section: Introductionmentioning
confidence: 92%
“…Hoa et al showed that, at low pressure, the condensation of SO 2 and NO 2 with water resulted in the formation of H 2 SO 4 and HNO 3 , which led to strong pitting and localized corrosion in the presence of H 2 SO 4 , while HNO 3 induced only high general corrosion. This might be related to different corrosion mechanisms as both Hoa et al and Morland et al suggested, but it could also be an indication of a difference in solubility.…”
Section: Introductionmentioning
confidence: 92%
“…Since the experiments were carried out below the dew point of H 2 SO 4 , presumably small acid droplets were formed in the atmosphere [33,34]. Further evidence of the acid formation and the catalytic role of NO 2 have been further proved, even under higher pressure by recent works from Morland et al [35][36][37]. These acids condensed at the specimen's surface, being the coldest point in the system due to the Peltier element underneath.…”
Section: In-situ Corrosion Experimentsmentioning
confidence: 99%
“…Corrosion and impurity reactions can form solid and liquid phases [3][4][5]. These products (solids, liquids) may separate from the CO 2 bulk phase due to density differences and either stick to the wall or follow the CO 2 stream.…”
Section: Sampling Locationmentioning
confidence: 99%
“…Due to the large number of possible impurities, the number of possible chemical reactions is high. The most important reactions that were identified in the Kjeller dense phase CO 2 project (KDC) [3,4,9,15,21] were…”
Section: Reactionsmentioning
confidence: 99%
See 1 more Smart Citation